Analysis of Multi-Business Cooperative Financial Reports at the Dharma Shanti Cooperative in Rama Agung Village, North Bengkulu Regency - Handayani, Dewa Ayu Made Dewi; Susena, Karona Cahya; Fitriano, Yun (Journal of Management, Economic, and Accounting, 2025)
The purpose of this study was to determine the Multipurpose Financial Statements at Dharma Shanti Cooperative to evaluate the financial health of cooperatives in the balance sheet, income statement, cash flow statement, statement of financial position and notes to financial statements.This type of research is descriptive and comparative method. The data analysis technique used is a qualitative method, namely the theoretical concept and description of the research object of the Multipurpose Cooperative (KSU) from the research results by collecting financial data made by the dharma shanti cooperative.This study analyzes financial reports related to loan and business activities for the period 2023 at the Dharma Shanti Cooperative located in Rama Agung Village, North Bengkulu Regency. By examining the balance sheet, income statement, cash flow statement, statement of financial position, and notes to the financial statements, and this research identified key trends, potential risks, and areas for improvement.